2008
DOI: 10.1159/000131886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micronutrient Supplementation on Mood in Nursing Home Residents

Abstract: One third of older people in nursing and/or residential homes have significant symptoms of depression. In younger people, deficiencies in selenium, vitamin C and folate are associated with depression. This study examines the association between micronutrient status and mood before and after supplementation. The objective was to determine whether the administration of selenium, vitamin C and folate improved mood in frail elderly nursing home residents. Mood was assessed using the Hospital Anxiety and Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 86 publications
2
53
0
Order By: Relevance
“…Collectively, the studies by Benton & Cook (1991), Hawkes & Hornbostel (1996), Finley & Penland (1998), Rayman et al (2005), and Gosney et al (2008) support this concept: improvements in mood or depression scores with supplementation were noted when the participants’ baseline selenium status was low, and no improvements were observed when the baseline selenium status was judged higher (Hawkes & Hornbostel (1996), Rayman et al (2005)). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Collectively, the studies by Benton & Cook (1991), Hawkes & Hornbostel (1996), Finley & Penland (1998), Rayman et al (2005), and Gosney et al (2008) support this concept: improvements in mood or depression scores with supplementation were noted when the participants’ baseline selenium status was low, and no improvements were observed when the baseline selenium status was judged higher (Hawkes & Hornbostel (1996), Rayman et al (2005)). …”
Section: Discussionmentioning
confidence: 94%
“…In addition to having cardiometabolic effects, there has been suggestion in review articles that selenium has potentially mood modulating effects (Bodnar & Wisner, 2005; Kaplan et al, 2007; Leung & Kaplan, 2009) as a few small studies (Benton & Cook, 1991; Finley & Penland, 1998; Gosney et al., 2008) do suggest a beneficial effect on mood. Recently, lower selenium levels were associated with higher depressive symptoms in an elderly, rural Chinese cohort (Gao et al, 2012) after adjusting for demographic and medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Gosney et al [20] observed that an 8-week course of selenium supplementation significantly improved mood in both residential and nursing home residents. This effect was allied with increased concentration of selenium in the serum.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Further, selenium added to the diet also reduced the anxiety in hospitalized patients who are elderly, cancer patients, and/or HIV patients [4749]. …”
Section: Nutritional Approaches For Anxietymentioning
confidence: 99%